Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3390/s22145200
|View full text |Cite
|
Sign up to set email alerts
|

Towards Multiplexed and Multimodal Biosensor Platforms in Real-Time Monitoring of Metabolic Disorders

Abstract: Metabolic syndrome (MS) is a cluster of conditions that increases the probability of heart disease, stroke, and diabetes, and is very common worldwide. While the exact cause of MS has yet to be understood, there is evidence indicating the relationship between MS and the dysregulation of the immune system. The resultant biomarkers that are expressed in the process are gaining relevance in the early detection of related MS. However, sensing only a single analyte has its limitations because one analyte can be inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 193 publications
0
5
0
Order By: Relevance
“…The measurement results in this work are represented as a resistor and CPE in series. The impedance of the sensor is defined as in (3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The measurement results in this work are represented as a resistor and CPE in series. The impedance of the sensor is defined as in (3).…”
Section: Resultsmentioning
confidence: 99%
“…Point-of-care biosensors present a promising solution for the regular monitoring of biomarkers for the early diagnosis of diseases like cancer [ 1 ], Alzheimer’s disease [ 2 ] and metabolic disorders [ 3 ]. Biosensors employ either a labeled approach or a label-free approach as the underlying principle.…”
Section: Introductionmentioning
confidence: 99%
“…Fiber-optic biosensors have garnered much attention owing to their high aspect ratio footprint, remote sensing capability, and ease of multiplexing [ 167 , 168 , 169 , 170 , 171 , 172 , 173 ]. Our research group developed a gold nanoparticle-coated optical fiber and demonstrated its application as an LSPR sensor for plant salicylic acid (SA) detection [ 20 ].…”
Section: Existing Optical Sensing Technologies To Monitor Plant-micro...mentioning
confidence: 99%
“…Interest in real-time monitoring systems for health status is a rising technological field, especially biomarkers for metabolites such as glucose, uric acid, lactic acid, and cholesterol. [1] Lactate is among the major biomarkers; it is formed from pyruvate in the process of anaerobic glycolysis, then passes into the blood, and then secreted in the form of sweat. [2] Moreover, lactate is considered a hypoxia marker in cells, tissues, and biological fluids.…”
Section: Introductionmentioning
confidence: 99%